Agroclimatic Risk Zoning of Papaya (Carica papaya L.) in the Hydrographic Basin of Paraná River III, Brazil - Caldana, Nathan Felipe da Silva; Nitsche, Pablo Ricardo; Ferreira, Luiz Gustavo Batista; Martelócio, Alan Carlos; Zaccheo, Paulo Vicente Contador; Martins, Jorge Alberto (Revista Agrogeoambiental, 2020)
Brazil is the largest producer and consumer of papaya (Carica papaya L.) in the world. Despite modern technological and scientific advances, climate is still the most important meteorological variable in agricultural production. In this context, agroclimatic risk zoning should be one of the first things to be considered when planning cultivation. The purpose of this study was to carry out climatic risk zoning for papaya cultivation in the Basin of Paraná River III, Paraná state, Brazil. Were used meteorological data from 1976 to 2018, collected from 43 stations. The climatic risk analysis was based on the precipitation, water balance, average annual temperature, average insolation, and frost tolerance required for papaya cultivation. The occurrence of frosts is the key limiting factor for production in the study area. This meteorological factor limits the viability of papaya cultivation in the Center-East region of the Basin. In other areas, risk remains, however, the papaya is apt for cultivation.